Tertiary Lymphoid Structures and B cells: Clinical impact and therapeutic modulation in cancer. (April 2020) - Sautès-Fridman, Catherine; Verneau, Johanna; Sun, Cheng-Ming; Moreira, Marco; Chen, Tom Wei-Wu; Meylan, Maxime; Petitprez, Florent; Fridman, Wolf Herman
Highlights: TLS are active sites for the generation and activation of adaptive immune responses in tumors. B cells and TLS have a favorable impact on patient's prognosis and response to immunotherapy. The impact of the T cells infiltrate on the prognostic value of B cells is tumor dependent. Chemotherapy and immunotherapy induce TLS formation. B cells may function via antigen-presentation, antibody production and generation of memory cells. Abstract: Tumors progression is under the control of a heterogeneous microenvironment composed of immune cells, fibroblasts, blood and lymphatic vessels, in which T cells have been demonstrated to be major actors, through their cytotoxic and cytokine producing effector functions and their long term memory that protects against metastasis. In this scenario, lessons from mouse models taught that B cells exert a protumoral role, via macrophage-dependent activation of inflammation. However, it became progressively evident from studies in patients with human cancers that the anti-tumor responses can be generated and controlled in tertiary lymphoid structures (TLS) that concentrate most of the intratumoral B cells and where B cells can differentiate into plasma cells and memory cells. Furthermore, recent studies demonstrated that the presence in tumors of B cells and TLS are associated with favorable outcome in patients treated by immunotherapy, unraveling TLS as a new predictive marker of anti-tumor response human cancers. This review encompasses the characteristics and functions of TLS and of B cells in human tumors, their prognostic and theranostic impact and summarizes the mouse models used to induce TLS neogenesis in tumors.